TV fiction and the heartthrobs from brazilian telenovelas between feminism and male chauvinism: a study case on José Mayer (Comunicação & Inovação, 2017)
This article presents a case study on the heartthrob leading man José Mayer. By problematizing machismo we discuss in which ways our time is able to press the tele-dramaturgical genre to transform fundamental standards. Through a dialogical analysis, we conclude that it is feasible to see significant changes in the composition of the heartthrob leading man and in the happy endings." The dialogue between fiction and reality forces changes in the aesthetic forms and cultural practices.
Keywords: Brazilian telenovelas. Heartthrob. Romantic love.